2001
DOI: 10.1101/lm.40501
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of PACAP-38 on Synaptic Responses in Rat Hippocampal CA1 Region

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP-38) is a member of the vasointestinal polypeptide (VIP)/secretin/glucagon family of neuropeptides for which neuroregulatory functions have been postulated. PACAP-38 receptors are expressed in different brain regions, including hippocampus. In this study, we examined the dose-dependent effects of PACAP-38 on the excitatory postsynaptic field potential (fEPSP) evoked at the Schaffer collateral-CA1 synapse in rat hippocampal slices. Bath application of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…It has been reported that a low dose of PACAP38 may influence synaptic transmission through the regulation of NMDARs (20). NMDAR activation has also been shown to result in GluA1 T840 dephosphorylation (16,17).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that a low dose of PACAP38 may influence synaptic transmission through the regulation of NMDARs (20). NMDAR activation has also been shown to result in GluA1 T840 dephosphorylation (16,17).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the GluA1 T840 site is less well characterized. PKC, calcium/calmodulin-dependent protein kinase II, protein phosphatase 1/2A (PP1/PP2A), and NMDAR activity have been reported to regulate GluA1 T840 phosphorylation (15-17).GluA1 T840 phosphorylation has also been found to enhance channel conductance (18).PACAP38 (pituitary adenylate cyclase activating polypeptide 38) is a neuropeptide that has been shown to regulate hippocampal CA1 synaptic strength (19)(20)(21)(22). PACAP38 can bind to and activate three different G protein coupled receptors, the PAC1, VPAC1, and VPAC2 receptors, which can lead to elevated cyclic AMP and Ca 2+ levels, and activation of phospholipase C and phospholipase D (23).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, another study showed that the application of PACAP38 enhanced AMPA-evoked currents (Michel et al, 2006). PACAP38 has been also shown to induce a form of long-term depression (LTD) in hippocampal neurons that requires interaction of AMPA receptor subunits with scaffolding proteins (Kondo et al 1997;Roberto et al 2001;Ster et al, 2009), thus validating its role in learning and memory. This has been further confirmed by the use of transgenic animals (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 97%